The Great Mogul - Tracy, Louis, 1863-1928; Chase, Joseph Cummings, 1878-1965 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Great Mogul" by Louis Tracy is a historical novel written in the early 20th century. The narrative unfolds against a backdrop of historical events in the late 16th century, focusing on the dire plight of Mirza Ali Beg, a Persian exile, and his family as they navigate the treacherous landscapes of Afghanistan in desperate search of a safe haven under the rule of the Great Mogul. The story intertwines themes of survival, sacrifice, and the fateful encounters that shape destinies, notably centering on the infant daughter whose future holds great significance. At the start of the novel, readers are introduced to Mirza Ali Beg and his wife, Mihr-ul-nisa, who are grappling with starvation as they traverse a harsh and unforgiving wilderness with their children. In a moment of desperation, they make an anguishing decision to abandon their newborn daughter in hopes that it will save the rest of the family. However, moments later, Mirza encounters a deadly snake threatening the baby and, in a dramatic turn, he rescues her. Their fortunes seem to change as they come across a caravan, leading to their eventual journey towards safety. The opening sets a poignant tone, illustrating themes of hope and despair while foreshadowing the intricate connections that will evolve throughout the story. (This is an automatically generated summary.)
Release date is 2010-10-26
E-text prepared by D Alexander and the Online Distributed Proofreading Team
Keywords: Mogul Empire -- Fiction